Analisis Pengaruh Fraud Hexagon terhadap Fraudulent Financial Reporting Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019 – 2022 - Matthew, Jason; Siregar, Anitaria (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
This study was conducted to analyze the effect of fraud hexagon on fraudulent financial reporting of transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2019 - 2022. The dependent variable in this study is fraudulent financial reporting using the Dechow F-Score measurement. The independent variables in this study are the six elements of the fraud hexagon (S.C.C.O.R.E) using the proxy’s financial stability, CEO education, government project, effective monitoring, change in auditor, and number of CEO's picture. This study used 88 samples from 22 transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2019 - 2022. The analysis method used is descriptive statistical analysis and logistic regression. The results showed that financial stability, effective monitoring, and change in auditors have an influence on fraudulent financial reporting. While CEO education, government projects, and the number of CEO's pictures have no influence on fraudulent financial reporting.